AKTIVITAS FITOHORMON INDOLE-3-ACETIC ACID (IAA) DARI BEBERAPA ISOLAT BAKTERI RIZOSFER DAN ENDOFIT - sukmadi, R bambang (Badan Pengkajian dan Penerapan Teknologi, 2012)
A total of 34 isolates of rhizosphere bacteria and endophytic bacteria have been isolated from several fruit and vegetable plants. Bacterial isolates were then screened to produce phytohormone indole-3-acetic acid (IAA) in a minimal medium (MM) with the addition of 1 g/l tryptophan as a precursor. Phytohormone production was carried out in an incubator shaker for 5 days at 28oC in a dark condition. IAA in the culture supernatant was extracted with ethyl acetate. The presence of IAA in the bacterial extract was detected using Thin Layer Chromatography (TLC). The concentration of IAA was determined quantitatively using High Performance LiquidChromatography (HPLC). The result showed that among 34 bacterial isolates, 20 isolates were able to produce IAA with different concentrations. The highest concentration of IAA (16,71 ppm) was produced by the endophytic bacteria isolated from twigs of starfruit plant. In addition, within the group of rhizosphere bacterial isolates, bacteria from kangkung plant was found to be the best one with IAA concentration of 10.99 ppm.